Preparation method of infrared hollow optical fiber
By adopting a double-layer dielectric film-metal film-quartz-based tube-protective film structure in infrared hollow fibers and using polyethylene glycol to assist in precipitation of silver films, the shortcomings of existing infrared hollow fibers in terms of transmission loss and bending loss are solved, and more efficient light energy reflection and transmission are achieved.
Patent Information
- Application Number
- CN202510292416.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-04-29
AI Technical Summary
The existing infrared hollow fibers have shortcomings in transmission loss and bending loss, and the roughness and height difference of the metal film are large, which affects the reflection efficiency of light energy.
The structure of a double-layer dielectric film-metal film-quartz-based tube-protective film is adopted, and the silver film is assisted with precipitation with polyethylene glycol to reduce the particle size of the metal particles and the roughness of the film, and a double-layer dielectric film is applied to the metal film to reduce transmission loss.
A more uniform, dense and smooth metal film is achieved, which improves the reflection efficiency of light energy, reduces transmission loss and bending loss, and improves the mechanical properties of quartz-based tubes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical fibers, in particular to a method for preparing an infrared hollow optical fiber. Background Art
[0002] Optical fiber is the abbreviation of optical fiber. It is a dielectric waveguide that works in the optical wave band. It uses the principle of total reflection to confine the electromagnetic wave energy in the form of light within its interface and guides the light wave along the axis of the optical fiber. According to different uses, it can be divided into two categories: one is used to transmit optical signals, namely communication optical fiber, and the other is used to transmit energy, namely energy transmission optical fiber.
[0003] With the development of laser technology, the application of infrared optical fiber is becoming more and more extensive, especially in communication engineering, industrial processing, military technology and medical equipment. In the infrared region, there are several very important lasers, such as 2.94μm Er: laser, 5.3μm CO laser and 9~11μm CO 2 Lasers, including 10.6μm CO 2 Due to the advantages of high conversion efficiency, large gain coefficient and high output power, lasers are widely used in industrial processing fields such as heat treatment, welding and cutting of material surfaces. They also have broad application prospects in infrared technology and scientific research fields such as automated operating systems, hazardous environments, mid-infrared spectrum signal transmission, infrared imaging, and infrared radiation temperature measurement, especially in the medical and health fields, which are even more important.
[0004] From the perspective of laser transmission performance, hollow-core optical fiber is more attractive than solid-core optical fiber. Hollow-core optical fiber can be divided into two types in structure: total reflection type and leakage type. The leakage type can greatly increase the reflection coefficient of the inner wall of the hollow-core optical fiber, overcome the loss caused by the large absorption rate k of the single-layer hollow core, and theoretically can obtain smaller transmission loss than the single-layer structure, and this type of optical fiber has better bending characteristics. Summary of the invention
[0005] The purpose of the present invention is to provide an infrared hollow optical fiber and a preparation method thereof to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: an infrared hollow optical fiber, wherein the structure of the infrared hollow optical fiber from inside to outside is: double-layer dielectric film-metal film-quartz substrate tube-protective film.
[0007] Furthermore, the double-layer dielectric film has a structure of a silver iodide layer and a polymethyl methacrylate layer.
[0008] Furthermore, the metal film is specifically a silver film.
[0009] Furthermore, the protective film is specifically a polymethyl methacrylate film.
[0010] Furthermore, a method for preparing an infrared hollow-core optical fiber comprises the following preparation steps: (1) Pre-treating the quartz substrate tube, then passing a 2 wt % palladium chloride aqueous solution at 10 mL / min, activating for 25 min, passing deionized water at 10 mL / min, and washing for 30 s to obtain a pre-treated quartz substrate tube; (2) Add 20 wt % ammonia solution to 1.75 wt % silver nitrate solution at 1-3 mL / s, stir at 20-40 rpm for 5-15 min, pass the solution and the reducing solution into the pretreated quartz substrate tube at 5 mL / min for 20-50 min, then wash with deionized water at 50 mL / min for 10 min, and then pass nitrogen at 10 mL / min until the inside of the substance is dry, to obtain a silver film quartz substrate tube; (3) Mix iodine and cyclohexane in a mass ratio of 0.2:100, heat to 50°C, stir at 50-100 rpm for 1-2 h, pass 5 mL / min into the silver film quartz substrate tube for 2-8 min, pass nitrogen at 10 mL / min until the inside of the material is dry, then immerse in 0.25 wt% polymethyl methacrylate-acetone solution, take out by the pulling method, and solidify to obtain an infrared hollow optical fiber.
[0011] Furthermore, the pretreatment method in step (1) is as follows: deionized water, ammonium hydroxide and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an alkaline solution; deionized water, hydrogen chloride and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an acid solution; the quartz substrate tube is cleaned in the order of deionized water-alkaline solution-acid solution-deionized water, the flow rate of deionized water is 40 mL / min, the flow rate of alkali and acid solution is 20 mL / min, each rinse is 15 minutes, and dried at 100°C for 1~2 hours.
[0012] Furthermore, the reducing solution in step (2) is prepared by mixing 10 wt % glucose aqueous solution, ethanol, polyethylene glycol 20000, and 2 wt % sulfuric acid aqueous solution in a mass ratio of 100:10:5:7.
[0013] Furthermore, it is characterized in that the mass ratio of the 20wt% ammonia solution to the 1.75wt% silver nitrate solution in step (2) is 1:8-12.
[0014] Furthermore, it is characterized in that the pulling speed in step (3) is 0.3 cm / s.
[0015] Furthermore, it is characterized in that the curing temperature in step (3) is 50-70° C. and the curing time is 100-150 min.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention utilizes polyethylene glycol to assist the metal film to precipitate inside the hollow quartz substrate tube, that is, utilizes polyethylene glycol with a high degree of polymerization to reduce the surface tension of the adsorbed solvent on the substrate tube surface through its active action, thereby increasing the effective area of the deposited metal, thereby reducing the particle size of the precipitated metal particles, reducing the height difference and roughness of the precipitated film, and making the prepared metal film more uniform, dense, and smooth. When the light wave is incident on the inside of the substrate tube, almost all the light energy can be reflected. Then, by coating a double-layer dielectric film on the metal film, the metal film is prevented from being While oxidizing, the transmission loss of the target wavelength is effectively reduced, and the bandgap characteristics of the multi-layer dielectric film are enhanced under the high reflection of the outer metal film, thereby reducing the additional loss during bending, so that the light beam is reflected on it, and the air is used as the transmission medium, so that the base tube reduces the reflection loss during energy coupling, the scattering loss during light transmission and the absorption loss. The second layer of dielectric film is to immerse the tube base in polymethyl methacrylate. After curing, it not only improves the transmittance in the infrared region, but also forms a protective film on the outside of the base tube, which improves the mechanical properties of quartz, thereby reducing the loss rate of the base tube. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods of various indicators of the infrared hollow-core optical fiber prepared in the following examples are as follows: Fiber performance: Take the same size of the embodiment and the comparative example, and use CO 2 The laser is tested for its linear loss power and bending loss power at a bending angle of 90° using the truncation method, and the output power is 50W.
[0019] Mechanical properties: The same size of the embodiment and the comparative example were taken to test the optical fiber tensile strength according to GB / T15972.31.
[0020] Example 1 (1) Deionized water, ammonium hydroxide, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an alkaline solution; deionized water, hydrogen chloride, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an acid solution; the quartz substrate tube is cleaned in the order of deionized water-alkaline solution-acid solution-deionized water, the flow rate of deionized water is 40 mL / min, the flow rate of alkali and acid solution is 20 mL / min, each rinse is 15 minutes, and dried at 100°C for 1 hour; then a 2wt% palladium chloride aqueous solution is passed at 10 mL / min, activated for 25 minutes, and deionized water is passed at 10 mL / min for 30 seconds to obtain a pretreated quartz substrate tube; (2) 10 wt% glucose aqueous solution, ethanol, polyethylene glycol 20000, and 2 wt% sulfuric acid aqueous solution were mixed in a mass ratio of 100:10:5:7 to obtain a reducing solution; 20 wt% ammonia aqueous solution was added to 1.75 wt% silver nitrate aqueous solution at 1 mL / s, stirred at 20 rpm for 5 min, and passed through the pretreated quartz substrate tube with the reducing solution at 5 mL / min for 20 min, then washed with deionized water at 50 mL / min for 10 min, and then nitrogen was passed through the material at 10 mL / min until the inside was dry to obtain a silver film quartz substrate tube; the mass ratio of the 20 wt% ammonia aqueous solution to the 1.75 wt% silver nitrate aqueous solution was 1:8; (3) Iodine and cyclohexane were mixed in a mass ratio of 0.2:100, heated to 50°C, stirred at 50 rpm for 1 h, and introduced into the silver film quartz substrate tube at 5 mL / min for 2 min. Nitrogen was introduced at 10 mL / min until the inside of the material was dry. The material was then immersed in a 0.25 wt% polymethyl methacrylate-acetone solution, pulled out at 0.3 cm / s, and cured at 50°C for 100 min to obtain an infrared hollow optical fiber.
[0021] Example 2 (1) Deionized water, ammonium hydroxide, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an alkaline solution; deionized water, hydrogen chloride, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an acid solution; the quartz substrate tube is cleaned in the order of deionized water-alkaline solution-acid solution-deionized water, the flow rate of deionized water is 40 mL / min, the flow rate of alkali and acid solution is 20 mL / min, each rinse is 15 minutes, and dried at 100°C for 1.5 hours; then, a 2wt% palladium chloride aqueous solution is passed at 10 mL / min, activated for 25 minutes, and deionized water is passed at 10 mL / min for 30 seconds to obtain a pretreated quartz substrate tube; (2) 10 wt% glucose aqueous solution, ethanol, polyethylene glycol 20000, and 2 wt% sulfuric acid aqueous solution were mixed in a mass ratio of 100:10:5:7 to obtain a reducing solution; 20 wt% ammonia aqueous solution was added to 1.75 wt% silver nitrate aqueous solution at a rate of 1-3 mL / s, stirred at 30 rpm for 10 min, and passed through a pretreated quartz substrate tube with the reducing solution at a rate of 5 mL / min for 30 min, then washed with deionized water at a rate of 50 mL / min for 10 min, and then nitrogen was passed through at a rate of 10 mL / min until the inside of the substance was dry, to obtain a silver film quartz substrate tube; the mass ratio of the 20 wt% ammonia aqueous solution to the 1.75 wt% silver nitrate aqueous solution was 1:10; (3) Iodine and cyclohexane were mixed in a mass ratio of 0.2:100, heated to 50°C, stirred at 75 rpm for 1.5 h, and introduced into the silver film quartz substrate tube at 5 mL / min for 5 min. Nitrogen was introduced at 10 mL / min until the inside of the material was dry. The material was then immersed in a 0.25 wt% polymethyl methacrylate-acetone solution, pulled out at 0.3 cm / s, and cured at 60°C for 125 min to obtain an infrared hollow optical fiber.
[0022] Example 3 (1) Deionized water, ammonium hydroxide, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an alkaline solution; deionized water, hydrogen chloride, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an acid solution; the quartz substrate tube is cleaned in the order of deionized water-alkaline solution-acid solution-deionized water, the flow rate of deionized water is 40 mL / min, the flow rate of alkali and acid solution is 20 mL / min, each rinse is 15 minutes, and dried at 100°C for 2 hours; then a 2wt% palladium chloride aqueous solution is passed at 10 mL / min, activated for 25 minutes, and deionized water is passed at 10 mL / min for 30 seconds to obtain a pretreated quartz substrate tube; (2) 10 wt% glucose aqueous solution, ethanol, polyethylene glycol 20000, and 2 wt% sulfuric acid aqueous solution were mixed in a mass ratio of 100:10:5:7 to obtain a reducing solution; 20 wt% ammonia aqueous solution was added to 1.75 wt% silver nitrate aqueous solution at 3 mL / s, stirred at 40 rpm for 15 min, and passed through a pretreated quartz substrate tube with the reducing solution at 5 mL / min for 50 min, then washed with deionized water at 50 mL / min for 10 min, and then nitrogen was passed through at 10 mL / min until the inside of the substance was dry to obtain a silver film quartz substrate tube; the mass ratio of the 20 wt% ammonia aqueous solution to the 1.75 wt% silver nitrate aqueous solution was 1:12; (3) Iodine and cyclohexane were mixed in a mass ratio of 0.2:100, heated to 50°C, stirred at 100 rpm for 2 h, introduced into the silver film quartz substrate tube at 5 mL / min for 8 min, and nitrogen was introduced at 10 mL / min until the inside of the material was dry. Subsequently, the material was immersed in a 0.25 wt% polymethyl methacrylate-acetone solution, pulled out at 0.3 cm / s, and cured at 70°C for 150 min to obtain an infrared hollow optical fiber.
[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: 10wt% glucose aqueous solution, ethanol, and 2wt% sulfuric acid aqueous solution are mixed in a mass ratio of 100:10:7 to obtain a reducing solution; 20wt% ammonia aqueous solution is added to 1.75wt% silver nitrate aqueous solution at 1~3mL / s, stirred at 30rpm for 10min, and both the reducing solution and the pretreated quartz substrate tube are passed at 5mL / min for 30min, then washed with deionized water at 50mL / min for 10min, and nitrogen is passed at 10mL / min until the inside of the material is dry to obtain a silver film quartz substrate tube; the mass ratio of the 20wt% ammonia aqueous solution to the 1.75wt% silver nitrate aqueous solution is 1:10; the remaining steps are the same as Example 2.
[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (3) is different. Step (3) is changed to: immerse the silver film quartz substrate tube in 0.25wt% polymethyl methacrylate-acetone solution, pull it out at 0.3cm / s, and cure it at 60°C for 125min to obtain an infrared hollow optical fiber; the remaining steps are the same as Example 2.
[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: iodine and cyclohexane are mixed in a mass ratio of 0.2:100, the temperature is raised to 50° C., and stirred at 75 rpm for 1.5 h. The mixture is introduced into the silver film quartz substrate tube at 5 mL / min for 5 min. Nitrogen is introduced at 10 mL / min until the inside of the substance is dry, thereby obtaining an infrared hollow optical fiber. The remaining steps are the same as those in Example 2.
[0026] Effect example Table 1 below shows the performance analysis results of the infrared hollow-core optical fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0027] Table 1 From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses polyethylene glycol to assist the metal film to precipitate inside the hollow quartz substrate tube, that is, polyethylene glycol with a high degree of polymerization is used to reduce the surface tension of the adsorbed solvent on the substrate tube surface through its active effect, increase the effective area of the deposited metal, and then reduce the particle size of the precipitated metal particles, reduce the height difference and roughness of the precipitated film, and make the prepared metal film more uniform, dense and smooth. When the light wave is incident on the inside of the substrate tube, almost all the light energy can be reflected. Then, by coating a double-layer dielectric film on the metal film, the metal is prevented from oxidation. At the same time, the transmission loss of the target wavelength is effectively reduced, and the bandgap characteristics of the multi-layer dielectric film are enhanced under the high reflection of the outer metal film, thereby reducing the additional loss during bending, so that the light beam is reflected on it, and the air is used as the transmission medium, so that the base tube reduces the reflection loss during energy coupling, the scattering loss and the absorption loss during light transmission. The tube base is immersed in polymethyl methacrylate, and after curing, a second layer of dielectric film is formed inside the tube base to improve the transmittance in the infrared region, and a protective film is formed outside the base tube to improve the mechanical properties of quartz, thereby reducing the loss rate of the base tube.
[0028] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an infrared hollow-core optical fiber, characterized in that: The method comprises the following preparation steps: (1) Deionized water, ammonium hydroxide, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an alkaline solution; deionized water, hydrogen chloride, and hydrogen peroxide are mixed in a mass ratio of 5:1:1 to obtain an acid solution; the quartz substrate tube is cleaned in the order of deionized water-alkaline solution-acid solution-deionized water, the flow rate of deionized water is 40 mL / min, the flow rate of alkali and acid solution is 20 mL / min, each rinse is 15 minutes, and dried at 100°C for 1.5 hours; then, a 2wt% palladium chloride aqueous solution is passed at 10 mL / min, activated for 25 minutes, and deionized water is passed at 10 mL / min for 30 seconds to obtain a pretreated quartz substrate tube; (2) 10 wt% glucose aqueous solution, ethanol, polyethylene glycol 20000, and 2 wt% sulfuric acid aqueous solution were mixed in a mass ratio of 100:10:5:7 to obtain a reducing solution; 20 wt% ammonia aqueous solution was added to 1.75 wt% silver nitrate aqueous solution at a rate of 1-3 mL / s, stirred at 30 rpm for 10 min, and passed through a pretreated quartz substrate tube with the reducing solution at a rate of 5 mL / min for 30 min, then washed with deionized water at a rate of 50 mL / min for 10 min, and then nitrogen was passed through at a rate of 10 mL / min until the inside of the substance was dry, to obtain a silver film quartz substrate tube; the mass ratio of the 20 wt% ammonia aqueous solution to the 1.75 wt% silver nitrate aqueous solution was 1:10; (3) Iodine and cyclohexane were mixed in a mass ratio of 0.2:100, heated to 50°C, stirred at 75 rpm for 1.5 h, and introduced into the silver film quartz substrate tube at 5 mL / min for 5 min. Nitrogen was introduced at 10 mL / min until the inside of the material was dry. The material was then immersed in a 0.25 wt% polymethyl methacrylate-acetone solution, pulled out at 0.3 cm / s, and cured at 60°C for 125 min to obtain an infrared hollow optical fiber.